PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 7 PEKANBARU - Ramadhani, Sarah; Alpusari, Mahmud; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research aims to improve IPA learning outcomes in IPA of student through the application inquiry learning models in class V students of SD Negeri 7 Pekanbaru. The low yield V grade students of SD Negeri 7 Pekanbaru in IPA learning is not exact due to the learning model used by teachers in the learning process. Students become passive and lazy to learn because the learning system that occurs simply by using methods lectures, discussion, and assignments. Research was conducted in the first semester of the academic year 2015/2016 in SD Negeri 7 Pekanbaru. Design research is classaction research. This study was conducted in two cycles. The procedure is carried out research including planning, implementation, observation and reflection. The research subjects are students of class V with the number of students altogether 25 people, which is 10 men and 15 women. Instruments and data used in this study is the observation sheet to assess the activities of teachers and students, as well as the activity of the test in the form of daily tests each cycle to measure student learning outcomes. The results showed the activities of teachers and students during the implementation process of inquiry learning has increased at each meeting. Increased activity of studying the impact on student learning outcomes. Learning outcomes of students has increased every cycle, from classical completeness base score 44% (not finished) increased to 64% (not finished) in the first cycle and the second cycle increased to 100% (complete). In restating the first cycle students on average increased by 16% from an average score of 69.2 basis be 80.3 in cycle I. In the second cycle increased by 33% from the base score to 91.8 in the second cycle. This study concluded that the implementation of inquiry learning model can improve IPA learning outcomes of class V students in SD Negeri 7 Pekanbaru.Keywords: Inquiry Learning Models, IPA Learning Outcomes